Acute paracoccidioidomycosis worsened by immunosuppressive therapy due to a misdiagnosis of Crohn's disease. - Eduardo Mastrangelo Marinho Falcão; Manuela da Costa Medeiros; Andrea D Ávila Freitas; João Carlos de Almeida Soares; Maria Inês Fernandes Pimentel; Leonardo Pereira Quintella; Dayvison Francis Saraiva Freitas; Priscila Marques de Macedo; Antônio Carlos Francesconi do Valle (PLoS Neglected Tropical Diseases)
Paracoccidioidomycosis (PCM) is a systemic mycosis endemic in Latin America, mostly in Brazil. The involvement of the gastrointestinal tract is uncommon and usually associated with the acute form. Recently, a cluster of acute PCM cases has been described in Rio de Janeiro, Brazil. We report a 42-year-old male, resident of Rio de Janeiro, presenting chronic diarrhea and abdominal pain in the past 3 years, previously diagnosed as Chron´s disease. When immunosuppressive therapy was prescribed, the patient evolved with worsening of the previous symptoms in addition to odynophagia, 20 kg-weight loss, disseminated skin lesions, diffuse lymphadenopathy and adrenal insufficiency. Histopathological and mycological examination of a skin lesion were compatible with PCM. Itraconazole was prescribed in high doses (400 mg/day). After seven months of treatment, the patient presented with acute abdominal pain which led to an emergent appendectomy, revealing the presence of the fungus. After 24 months, the patient reached clinical cure and recovered from adrenal insufficiency. We emphasize the importance of PCM as a differential diagnosis in patients with chronic diarrhea. The risk of fungal infections should be considered prior to initiating immunosupressive therapies, particularly in endemic areas.